Kedudukan dan Kewenangan Dewan Perwakilan Daerah dalam Sistem Ketatanegaraan Indonesia - Salmon E.M. Nirahua (Fakultas Hukum Universitas Islam Indonesia, 2011)
Functioned as a regional representative council, DPD possessing a regional representative character principally has a broader representative character compared to DPR (Legislative Assembly). It is because its representative dimensions are based on all of the citizens living in the regions. The issues being studied include (1) Is the existence of DPD in line with the idea of its establishment based on the bicameral legislative system?, (2) Is the constitutional authority of DPD synchronic with its existence as a state institution? This is a normative research focused on primary and secondary materials of law including the regulation of law and the literatures relevant as the research object. In obtaining the primary and secondary materials, a library research was conducted by involving a descriptive-qualitativeanalysis. The research result then shows the existence of DPD in relationship with DPR and MPR as regulated in the Constitution of 1945 is not in line with the thought of its establishment. At this point, the reform on the structure of Indonesia Constitution toward a strong bicameralism is not materialized in the Constitution of 1945.